Strategic planning for public relations - Smith, Ronald D. 1948- (Routledge, 2017)
Strategic Planning for Public Relations is in its fifth edition of offering an innovative and clear approach for students looking to learn how to develop public relations campaigns. It is a text intended for those serious about entering the rapidly changing professions of public relations and strategic communication. Ronald Smith shows how to implement pragmatic, research-driven strategic campaigns used in public relations practice, and draws from his years of experience as a professional in the industry and his years of teaching in the classroom.